2016
DOI: 10.5935/1678-9741.20160037
|View full text |Cite
|
Sign up to set email alerts
|

Is age a determinant factor in EVAR as a predictor of outcomes or at procedure selection? Our experience

Abstract: IntroductionEndovascular aneurysm repair (EVAR) is the therapy of choice in high risk patients with abdominal aortic aneurysm. The good results described are leading to the broadening of clinical indications to younger patients. However, reintervention rates seem higher and even with successful treatment sometimes there is growth of the aneurysm sac and rupture, meaning a failure of the therapeutic goal. This study proposes to analyse the impact of age in patients' selection and post-EVAR results.MethodsThe cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…35 Abdominal aortic aneurysm is a disease of the elderly with median age at EVAR ranging from approximately 73-75 years. [36][37][38][39] The 5-year survival after EVAR ranges from 57%-75%. [40][41][42][43][44] Previous studies have shown that the majority of deaths after EVAR are due to non-surgical causes such as cardiovascular disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…35 Abdominal aortic aneurysm is a disease of the elderly with median age at EVAR ranging from approximately 73-75 years. [36][37][38][39] The 5-year survival after EVAR ranges from 57%-75%. [40][41][42][43][44] Previous studies have shown that the majority of deaths after EVAR are due to non-surgical causes such as cardiovascular disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In contrast, Machado et al. 20 reported no significant statistical differences in terms of mortality and re-interventions among different age group of patients who have undergone EVAR. 20…”
Section: Discussionmentioning
confidence: 95%
“…Este estudio realizado corresponde a la primera investigación retrospectiva y analítica realizada en nuestra ciudad sobre EVAR, y muestra los primeros 50 casos intervenidos, pretendiendo esclarecer el comportamiento de una técnica innovadora en nuestra región. En esta evaluación, la edad de los pacientes fue similar a lo reportado por Machado et al en el 2016 4 , pero el diámetro promedio de los aneurismas intervenidos en nuestro centro fue mayor en tamaño, comparado con las publicaciones de Manning et al 5 y Vallejo et al en un estudio colombiano 6 . Huang et al encontró que los pacientes con diámetros del aneurisma superiores a 6 cm, como nuestros pacientes, tenían mayor mortalidad, complicaciones y reintervenciones 7 .…”
Section: Discussionunclassified